#TITLE_ALTERNATIVE# - PURWA SANTIKA (NIM 10105060), ADITYA
Localization of rings has some powerful theorems to give criteria for equality of radicals of ideals. The construction of equalty criteria in some classes of rings(especially Noetherian rings) can be derived from the properties of their localization. The property of prime ideals and regular R-sequences is helpful on proving equality criteria.